THE REASONS OF STUDENTS’ RETICENCE IN ENGLISH EDUCATION STUDY PROGRAM - Irwanti, Emi; ., Ikhsanudin; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: Oral participation is essentially important in English classroom. The writer observed and found that the students of English Education Study Program, Tanjungpura University, tended to be reticent when classroom discussion occured. They chose to remain silent rather than participating actively in the discussion. This study aimed to investigate the reasons for students’ reticence in English classroom using case study method. The participants were 10 students of the 2nd semester students. The participants were chosen by the characteristics of reticence such as tending to be reluctant in responding lecturers’ or other students’ questions, sitting at the middle/back rows, and rarely asking questions (rarely raising hand). Using direct observation and semi-structured interview, the study found that the main reasons of students’ reticence were anxiety, shyness, unfamiliarity with the topics/materials, low English proficiency, fear of making mistakes, lacking confidence in oneself, and being underprepared. Based on the findings, it showed that affective, individual, and psychological factors had a great influence on students’ reticence. Keywords : Students’ Reticence, Reasons, English Education Abstrak: Partisipasi secara lisan sangat penting di kelas bahasa Inggris. Penulis mengamati and menemukan bahwa mahasiswa dari program studi pendidikan bahasa Inggris, universitas Tanjungpura, cenderung bersikap diam ketika diskusi kelas berlangsung. Mereka memilih untuk tetap diam daripada berkonstribusi di kelas. Penelitian ini bertujuan untuk menginvestigasi alasan-alasan mahasiswa menjadi bersikap diam di kelas bahasa Inggris menggunakan metode studi kasus. Peserta dari penelitian ini adalah 10 mahasiswa semester dua. Peserta ini dipilih berdasarkan kararteristik dari sikap diam yaitu cenderung menolak dalam merespon pertanyaan dosen atau mahasiswa yang lain, duduk di barisan tengah atau belakang, dan jarang bertanya (jarang mengangkat tangan). Dengan menggunakan pengamatan langsung dan interview semi-struktur, penelitian ini menemukan bahwa alasan utama mahasiswa bersikap pendiam adalah cemas, malu, tidak terbiasa dengan topik/materi, kemampuan Bahasa Inggris yang rendah, takut salah, kurang percaya diri, dan kurang persiapan. Berdasarkan hasil penelitian, dapat terlihat bahwa faktor afektif, faktor individual, dan faktor psikologi sangat mempengaruhi sikap diam mahasiswa. Kata kunci : Siswa Diam, Alasan-alasan, Pendidikan Bahasa Inggris